Tracking nitrate reducers and denitrifiers in the environment. (1st February 2005) - Philippot, L.
Abstract : The ability to respire nitrate when oxygen is limited has been described in taxonomically diverse microorganisms including members of the α-, β-, γ- and ε-proteobacteria, high and low GC Gram-positive bacteria and even Archaea. Respiratory nitrate reduction is the first step of the denitrification pathway, which is important since it is the main biological process responsible for the return of fixed nitrogen to the atmosphere, thus completing the nitrogen cycle. During the last decade, considerable knowledge has been accumulated on the biochemistry and genetics of the nitrate reductases. In this paper, we summarize the recent progress in molecular approaches for studying the ecology of the nitrate-reducing community in the environment.